Controlling Invasive Exotic Plants in North Florida Forests - Chris Demers; Patrick Minogue; Michael Andreu; Alan Long; Rick Williams (EDIS, 2016)
Of the more than 4,000 known plant species growing in Florida, approximately 30% are not native to Florida or the Southeast, and in the U.S., invasive exotic species cost an estimated $120 billion each year in damages. Early detection and removal of invasive plants is the key to successful management. This revised 13-page publication describes many of the current methods used in north Florida forest operations to manage invasive exotic plants. It also provides references for additional sources of information. Written by Chris Demers, Patrick Minogue, Michael Andreu, Alan Long, and Rick Williams, and published by the School of Forest Resources and Conservation, August 2016.